Joseph Anténor Firmin: Racial Equality, Solidarity, and Sovereign Body Politic - Kessler, Sally M. (Journal of Critical Race Inquiry)

(untitled) (Queen's University, 2024)
Joseph Anténor Firmin was a Haitian diplomat and scholar, Pan-Africanist, and an early participant in the birth of French anthropology. After long being neglected, Firmin’s articulations of Pan-Africanism in the Caribbean environment are finally receiving their due. In active correspondence with other thinkers of the African diaspora, Firmin was an early proponent of developing a Caribbean confederacy. Although his seminal anthropological study, The Equality of Human Races: Positivist Anthropology (1885), has received the most scholarly attention to date, his contextualization of Haiti on the world stage, developed in Mr. Roosevelt, President of the United States, and the Republic of Haiti (Mr. Roosevelt, président des États-Unis et la République d’Haïti, 1905) remains understudied to this day. Firmin situates his nation in the larger North American landscape of U.S. imperialism and Haiti’s longstanding ties to the French Republic to examine how to most rationally promote Haitian prosperity. His notions of political determination for African diasporic nations appear early in the timeline of the fields of anthropology and sociology. This article will explore Firmin’s contributions to history, anthropology, and self-determination of nations.